NEFT SHIǴINDILARINAN PAYDALANIP JASALMA JOL MENEN JANILǴI ALIW - Ajieva, M.B.; Artikov, M.B.; Ajieva, Z.B.; Sultonov, D.Q.; Bazarbaeva, L.G. (SCIENCE and SOCIETY, 2023)
This article highlights the theoretical issues of obtaining synthetic fuel from the remains of petroleum products using the chemical elements of halogens (fluorine, chlorine, bromine and iodine). The physical and chemical characteristics of oil and products obtained from oil are given, as well as the technological process of processing the final products of oil production. The article also pays great attention to the use of oil in the national economy.